Lijst hout; 36.5x43 cm.; glas. Gesigneerd. Origineel in archief Domela, los. Zie ook BG A4/10 - Kok, J.J.,
Lijst hout; 36.5x43 cm.; glas. Gesigneerd. Origineel in archief Domela, los. Zie ook BG A4/10.